MASS VARIATION LAWS BY HILL APPROXIMATION IN THE RESTRICTED THREE BODY PROBLEM WITH VARIABLE MASSES - Abayev, M.T. (Recent Contributions to Physics, 2008)
Laws of change of masses in the restricted problem of three bodies of variable masses by Hill approximation are considered. Nine laws of mass variation when masses of actively gravitating bodies are time dependent and changed isotropic rate various velocity.